IDDAH PERPEKTIF IMAM SYAMSUDDIN AL-SARAKHSI - Afiful Huda; Ahmad Zainal Ma’arip (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
One of the legal consequences of breaking up a marriage is the iddah that must be lived by the wife. This article will discuss the opinion of Imam Syamsuddin al-Sarakhsi, a prominent member of the Hanafyah school of thought regarding iddah. Al-Sarakhsi explained that it is not good for a woman who is divorced ba'in or raj'i to leave the house because she is still in her 'iddah period. For a woman whose husband has passed away, her Iddah is four months and ten days. In addition to having to comply with 'Iddah, a woman for a woman whose husband has left her must also carry out 'Ihdad. 'Ihdad is a condition where a wife must refrain or mourn for four months and ten days. During that time, the wife should express her grief by not adorning herself, not wearing perfume, not wearing eye shadow and not leaving the house. Al Mabsut also explained about the 'iddah of women who have reached puberty and women who have reached menopause and their daughters, whether they are free women or slaves who are not yet free. The iddah of a woman whose husband has died is not valid except with a valid marriage, whether married or not, whether she is young or old. Even if the woman is an independent Muslim woman or a married person. Among them said, women have 2 iddah namely long iddah for a year and short iddah for 4 months and 10 days, as Allah says in (QS. Al-Baqarah [2]: 240). The perfect Iddah is for one year, although it is sufficient for 4 months and 10 days as relief for the woman. Women are also allowed to leave the house during 'iddah when if the woman does not leave the house then she cannot provide for her life or that of her family.